The mGluR5 agonist CHPG enhances human oligodendrocyte differentiation - Huang, Yangyang; Geywitz, Celine; Bandaru, Anjalika; Glass, Ian A.; Schirmer, Lucas; Nobuta, Hiroko; Dreyfus, Cheryl F. (Acta Neuropathologica Communications, 2025)
Previous studies in adult mice indicate that the mGluR5 agonist 2-chloro-5-hydroxyphenyl glycine (CHPG), reduces cuprizone-elicited losses in myelin. This effect is partly mediated by CHPG binding to mGluR5 receptors on reactive astrocytes, triggering the release of brain derived neurotrophic factor (BDNF), which results in an increase in myelin. However, it remains unclear whether CHPG has similar beneficial effects on human oligodendrocytes. To address this issue, we examined effects of CHPG using both cultured human induced pluripotent stem cell (hiPSC)-derived oligodendrocytes and primary human fetal oligodendrocytes. We show that CHPG increases the proportion of MBP+ mature oligodendrocytes without affecting survival. This effect is mediated by increasing the proliferation of oligodendrocyte precursor cells (OPCs) and enhancing differentiation in young oligodendrocytes. In contrast to observations in mice, mGluR5 expression in humans is localized on PDGFRα+ OPCs and O4+ immature oligodendrocytes, but not astrocytes. Using purified human OPC cultures, we show a direct effect of CHPG in increasing the proportion of MBP+ mature oligodendrocytes. To identify potential cellular targets of CHPG in demyelinating disease, we analyzed postmortem tissue from individuals with chronic active multiple sclerosis (MS) and healthy controls. In contrast to the hiPSCs or primary oligodendrocytes, demyelinated white matter from MS patients shows elevated mGluR5 mRNA expression in astrocytes. Taken together, our findings suggest that CHPG enhances the differentiation of human OPCs through a mechanism distinct from that observed in cuprizone-treated mice. Moreover, astrocytes in MS pathology upregulate mGluR5, suggesting mGluR5 expression changes dynamically under disease conditions.